2000
DOI: 10.1007/s11663-000-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional monte carlo simulation of grain growth in the heat-affected zone of a 2.25Cr-1Mo steel weld

Abstract: We report here the first three-dimensional (3-D) Monte Carlo (MC) modeling of grain growth in the heat-affected zone (HAZ) of a weldment. Computed grain-size distributions in the HAZ of a 2.25Cr-1Mo steel, for different heat inputs in the range from 1.1 to 4.8 MJ/m, were compared to independent experimental results. The simulated mean grain size for different heat inputs agreed well with the corresponding independent experimental data. The mean grain size at various locations equidistant from the fusion line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Some Monte Carlo simulations on the grain growth in the HAZ demonstrated the existence of the thermal pinning [6][7][8]. However, the effects of temperature gradient on the grain growth were not systematically scrutinized and the detail of the thermal pinning remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Monte Carlo simulations on the grain growth in the HAZ demonstrated the existence of the thermal pinning [6][7][8]. However, the effects of temperature gradient on the grain growth were not systematically scrutinized and the detail of the thermal pinning remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this system has not been subjected to the detailed investigation, since the earlier Monte Carlo studies [6][7][8][9] focused on the grain growth where the growth exponent characterizing the temporal change of the average grain size deviates from 0.5 of the ideal case.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances were made by Debroy et al with a three-dimensional (3D) weld simulation. [12][13][14][15] Their studies demonstrated good agreement with experimental grain size distributions at various distances from the centerline of the FZ. Debroy and co-workers focused their analysis on the heat-affected zone (HAZ) surrounding the FZ and excluded the FZ from their simulation domain.…”
Section: Introductionmentioning
confidence: 53%
“…Among the computational models, Monte GRAIN-SIZE changes during processing of metals and Carlo (MC) simulation [7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22] has been widely used to simalloys may affect their strength, toughness, ductility, and ulate grain growth under both isothermal and nonisothermal corrosion resistance. [1] As a result, the prediction and control conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical models have been developed to undernotable exceptions include some recent works, where calcustand the effects of time and temperature on the grain-size lations were done in three dimensions. [8,14,15,[20][21][22] changes. These models often describe grain growth by the There are considerable computational challenges in confollowing parabolic equation, derived by considering growth ducting meaningful MC calculations.…”
Section: Introductionmentioning
confidence: 99%